Salaries in Science: Dynamics and Priorities of Soviet Policy - Dolgova, Evgeniya A. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2025)
This article characterises the salary changes in the field of science during the Soviet period. The author puts forward a hypothesis that the changes in salaries fixed in regulatory documents reflect long-term trends in science policy and conscious decisions of the authorities to distribute resources between different groups (qualification, territorial, representatives of academic, university, and branch science, etc.). Characterising changes in salaries, the author concludes that 1) in Soviet science, the dominant line was not the individual economic motivation of a researcher, but the support of research teams affiliated with the sector (academic, university, branch science) or particular organisation; 2) the processes of stratification of the Soviet scientific community were of a hidden nature, implying the absence of a competitive distribution of resources, i. e. attempts to stimulate the individual efficiency of scientists were of a “punitive” rather than “incentive” nature; 3) wage regulation was an ineffective tool of scientific policy in conditions of the discrepancy between real and nominal wages in the field of science, inflationary processes, differences in the commodity value of the rouble for different groups, and the lack of transparency in the Soviet economy. In this respect, the assessment of the principle of material incentives for labour in science should be of a comprehensive nature, taking into account the whole range of practices of both financial and social and welfare support of science. The study draws upon a wide range of sources from the State Archive of the Russian Federation and the Russian State Archive of Contemporary History, including those introduced into the academic circulation for the first time.